Proceedings of the 2nd Czech-China Scientific Conference 2016 - Gottvald, Jaromir; Praus, Petr (IntechOpen, 2017)
This book comprises the proceedings of the 2nd Czech-China Scientific Conference 2016 which was held on 7th June 2016 in Ostrava, Czech Republic. The objective of the conference was to present the latest achievements in the fields of advanced science and technology that stem from research activities of VŠB - Technical University of Ostrava and its Chinese partners. The conference was multi-topical, which allowed also young researchers from different scientific areas to present their findings and to get the feel of an international conference atmosphere. The conference attracted specialists from the areas of economy, safety in civil engineering and industry, material technologies, environment and computational science. The conference structure corresponds with structure of the articles.